Transforming Computer Network Learning: The Role of Animation Media in Developing Students' Understanding of Abstract Material - Zamzuri, Anwar; Hasan, Mohd (Universitas Amikom Purwokerto, 2024)
The Malaysian Polytechnic's job is to supply the nation with semi-skilled labor to meet its demands. Numerous study programs, such as the Sequence Systems Diploma program, whose material is integrated with the CISCO professional certification program, have been established for this aim. This effort is in response to industry demand for skilled labor. However, based on examination decisions made by students, it was discovered that there might be shortcomings in the way this subject—which has a lot of abstract content—is taught, which could affect how well students do. This working paper proposes a transformation towards the use of new media such as animation, which has been proven through the study to be effective in depicting abstract lesson content to students. In this regard, a pilot study has been conducted among the teaching staff of this subject to identify the problems being faced. The results of a pilot study carried out in the form of interviews found that teaching staff actually faced problems in understanding students' abstract content in the form of lectures alone. This is because creating a workforce that is semi-skilled, competent, and capable of competing in the more demanding workplace of today requires a precise grasp of the contents of this abstract knowledge.